JAPANESE DIPLOMACY WITHIN ASEAN REGIONAL FORUM (ARF): SOME ASPECTS OF THE REGIONAL SECURITY - O. V. Lebedeva (Vestnik MGIMO-Universiteta)
The article is devoted to the issue of Japan policy in South-East Asia specifically to Japanese diplomacy within ASEAN Regional Forum (ARF). ARF created in 1994 was the first multilateral forum were regional security issues of Southeastern countries could be discussed. Japan took part in creation of the Forum and is its active participant. Since mid 90th Japanese diplomacy used ASEAN Regional Forum platform to promote its own national security interests in addition to other bilateral and multilateral activities. One of the first subjects for discussion at ARF was China nuclear activity and nuclear tests. The issues of constant concern remain territorial disputes in East China Sea and South China Sea. Specific regional topics like China-Taiwan relations, Cambodia, ideas for Northeastern Asian security forum, India and Pakistan nuclear tests, Asian financial crisis of the 90th were also in focus of ARF discussions. Annual sessions of the Forum gave Japan opportunity to articulate concerns, promote its interests and negotiate topics on bilateral level. Of vital security concern for Japan was and remains to exist North Korean nuclear program. For the last two decades the country took a great activity in the work of ASEAN Regional Forum and it could be stated that ARF remains to be an important mechanism for Japan diplomacy to address important issues security and stability in Southeastern Asia.